Lance and Other Gifted and Talented Students of Color Matter: Five Models and Theories to Guide Early Childhood Educators in Advancing Equity. Issue 1 (January 2021) - Ford, Donna Y.; Wright, Brian L.; Tyson, Cynthia A.
This article focuses on essential models and theories to help early childhood educators (ECE) in understanding and teaching non-White gifted and talented (GATE) students. The focus is on minoritized students who have been formally identified and those who should be identified (i.e., are underrepresented). These models and theories are crucial in the recruitment and retention process as well as preventing and reversing underachievement.